2020
DOI: 10.3343/alm.2020.40.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of optrA-Mediated Linezolid-Nonsusceptible Enterococcus faecalis in a Tertiary Care Hospital

Abstract: This study investigated resistance mechanisms and epidemiology of emerging linezolidnonsusceptible Enterococcus faecalis (LNSEF) in a tertiary care hospital. LNSEF isolated from clinical samples were collected from November 2017 to June 2019. The isolates were investigated for linezolid resistance and the associated molecular mechanisms, including mutations of 23S rRNA domain V and acquisition of the cfr or optrA resistance gene. We used pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
(33 reference statements)
2
9
1
Order By: Relevance
“…The present detection rate of optrA in E. faecalis in Bangladesh (2.4%) may be comparable to those reported in China, implying relatively high prevalence among clinical isolates in this country, and may suggest also the potential distribution among the healthy population since LZD has been rarely used. The occurrence of optrA-positive E. faecalis was reported also in patients having no history of LZD treatment in Korea [48]. Because the five LZD-non-susceptible isolates in our study exhibited resistance to multiple drugs including NIT, it is possible that these isolates might have occurred by selection with ordinary antimicrobial treatment.…”
Section: Discussionsupporting
confidence: 54%
“…The present detection rate of optrA in E. faecalis in Bangladesh (2.4%) may be comparable to those reported in China, implying relatively high prevalence among clinical isolates in this country, and may suggest also the potential distribution among the healthy population since LZD has been rarely used. The occurrence of optrA-positive E. faecalis was reported also in patients having no history of LZD treatment in Korea [48]. Because the five LZD-non-susceptible isolates in our study exhibited resistance to multiple drugs including NIT, it is possible that these isolates might have occurred by selection with ordinary antimicrobial treatment.…”
Section: Discussionsupporting
confidence: 54%
“…The common mechanisms of Enterococcus resistance to linezolid include point mutations in chromosome 23S rRNA genes or genes encoding L3, L4, and L22 ribosomal proteins ( Mendes et al, 2014 ; Wang et al, 2014 ). Other important mechanisms include plasmid-mediated chloramphenicol-florfenicol resistance cfr gene or ribosome protection gene optrA and poxtA ( Wang et al, 2014 ; Park et al, 2020 ; Ruiz-Ripa et al, 2020 ). Correspondingly, several mechanisms have been proposed to be related to fosfomycin resistance including fosfomycin forming an inactive adduct ( Falagas et al, 2018 ), fosfomycin modification enzyme ( Cassir et al, 2014 ), mutations in the chromosomal genes encoding fosfomycin transporters ( Fu et al, 2016 ; Xu et al, 2017 ) and mutations in the target enzyme MurA ( Falagas et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…ST16 was identified in three optrA -positive E. faecalis ; two isolates cocarried fexA, and one isolate has only optrA . This ST has been identified in food animals and humans in Korea and other countries and is known as an optrA -carrying clone with a worldwide distribution [ 11 , 19 ]. In addition, EFS17 isolated from pork was identified as ST585, which coharbored optrA and fexA .…”
Section: Discussionmentioning
confidence: 99%
“…The optrA , poxtA , and cfr encoding enterococci has been reported in Korea and many countries such as China, Italy, Ireland, and Malaysia [ 3 ]. In particular, it was confirmed that all enterococci isolated from tertiary hospital patients in Korea possessed the optrA gene, but none of them were treated with linezolid [ 11 ]. Therefore, it was estimated that the optrA -positive linezolid nonsusceptible enterococci appeared at the hospital through the community onset [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation